THE 'DAUGHTER OF THE NILGIRI MOUNTAINS': A STUDY ON THE SOCIAL SAGA OF DARING WOMAN. - Joseph, Predeep; R., Shani Ruskin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Akkamma Devi was born on 5 September 1918 in a small village tucked away in the hills of Nilgiris. She was educated at different schools in Coonoor, Tamil Nadu and she went on to do her BA in Economics at St Theresa's College, Ernakulum. Here she took an active part in the Quit India movement of 1942 with her close friends and classmates and she was arrested and detained. Her humble beginnings notwithstanding, she won the 1962 General Election with a thumping majority and became the first lady Member of Parliament from the Badaga community and the Nilgiri Constituency. She was the first woman to graduate from the Badaga community of the Nilgiris. She was a prominent social worker from the Nilgiris who provided outstanding services to rural womenfolk of the Nilgiris. She was a champion of women's cause. She was sure women could achieve laurels in any field and compete with men if given the correct guidance and education. She was able to mobilise the women in remote areas. Surely, she was worthy to be called the 'Daughter of the Nilgiri Mountains'.